Pembangunan Pedesaan ‘Endogen’: Kiprah KKN UIN Sunan Kalijaga di Karangdukuh Klaten - Muhammad Qowim (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2019)
Endogenous Rural Development is an application concept of Endogenous Regional Development in rural scale. This study portrays the progress of UIN Sunan Kalijaga Yogyakarta in supporting endogenous rural development in Karangdukuh Village, Jogonalan District, Klaten Regency. Continuing the progress of UIN Sunan Kalijaga 2017, this article empowers a peasant community named Sentra Peternakan Rakyat (SPR) in Kebon Wulang Reh, in Karangdukuh Village. This study was first elaborated through two FGD processes. The FGD process is the first step to understanding the expectations and mapping of SPR needs. After conducting the Particypatory Rural Appraisal (PRA) survey, the study in this article was carried out in 3 concrete actions, namely the development of ‘Cakruk Pintar’ at the SPR location, Health Promotion and Trial Learning in ‘Cakruk Pintar’. These three main variables are people’s livestock, public health, and community learning habitus. The results of the development of 'endogenous' village development in the community service process have an elaborative and collaborative spirit. The collaboration aspect is the entrance to invite practitioners so that they can generate positive reactions from the social community. Meanwhile, elaborative aspects can give birth to new dissemination from all stakeholders, partners and policy makers. Where this Participatory Action Research (PAR) village development process can succeed if there is academic sustainability, both programs can be continued or stopped.